Effects of Increasing Dietary Zinc in Low ABC-4 Diets on Nursery Performance, Fecal Dry Matter, Serum Zinc, and Zinc Excretion - Julian Arroyave; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Katelyn N. Gaffield; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2024)
With the potential negative impact of pharmacological levels of zinc (typically from zinc oxide; ZnO) on the environment and public health, it’s necessary to validate the doses commonly used in commercial swine production and evaluate new nutritional strategies to replace the use of pharmacological levels of Zn. A total of 360 pigs (initially 13.2 ± 1.63 lb) were used to evaluate the effects of increasing dietary Zn and the acid-binding capacity (ABC-4) of the diet on nursery pig performance, fecal dry matter, serum Zn, and Zn excretion. At weaning, pigs were randomly assigned within two body-weight blocks to one of the six dietary treatments in a randomized complete block design. There were five pigs per pen and 12 pens per treatment. Experimental diets were fed for the first 24 d (phases 1 and 2), and then all pigs were fed a common phase 3 diet for 22 d. All diets contained 110 ppm of Zn from ZnSO4 from the trace mineral premix. The control treatment consisted of a low ABC-4 diet (200 and 250 meq/kg from d 0 to 10 and d 10 to 24, respectively). The next four treatments were the control diet with increasing Zn at 500, 1,000, 2,000, and 3,000 ppm in phase 1, and 333, 666, 1,332, and 2,000 ppm in phase 2 using ZnO. The sixth treatment was a high-ABC-4 diet (493 and 470 meq/kg from d 0 to 10 and d 10 to 24, respectively) with 3,000 and 2,000 ppm of added Zn in phases 1 and 2, respectively from ZnO. In all periods, no differences (P > 0.10) were observed between the low- and high-ABC-4 diets when 3,000 and 2,000 ppm of Zn were added in phases 1 and 2, respectively. For the experimental period (d 0 to 24), ADG and ADFI increased (linear, P < 0.05) as dietary Zn increased, with no difference in F/G. For the overall period, no response (P > 0.10) to dietary Zn was observed for any of the performance criteria. For fecal dry matter, no significant effect of dietary Zn was observed at d 10 or 24 (P > 0.10). However, at d 10, low-ABC-4 diets had a higher (P = 0.002) fecal dry matter than the high-ABC-4 diets at the same dietary level of Zn. Zinc intake, fecal Zn excretion, and Zn absorption increased (quadratic, P < 0.001) as dietary Zn concentration increased. A trend was observed (linear, P = 0.074) as the apparent total tract digestibility (ATTD) of Zn was increased as dietary Zn concentration increased. Low-ABC-4 diets had higher (P < 0.05) Zn intake, absorption, and ATTD of Zn than the high-ABC-4 diet at the same dietary Zn concentration. No difference (P = 0.921) was observed for fecal Zn excretion between ABC-4 formulation strategies. Day 24 serum-Zn concentration increased (quadratic, P < 0.001) as dietary Zn increased and a marginal increase (P = 0.095) in favor of the low-ABC-4 diets was observed between the formulation strategies. In conclusion, lowering the dietary ABC-4 capacity of diets containing pharmacological levels of ZnO increased d 10 fecal dry matter, Zn absorption, and the ATTD of Zn. Increasing ZnO in low-ABC-4 diets improved ADG and ADFI during the experimental period. However, this did not translate into overall performance differences.
Keywords: acid binding capacity; fecal dry matter; growth performance; zinc excretion; zinc oxide